DRI-Grass: A New Experimental Platform for Addressing Grassland Ecosystem Responses to Future Precipitation Scenarios in South-East Australia - Power, Sally A.; Barnett, Kirk L.; Ochoa-Hueso, Raul; Facey, Sarah L.; Gibson-Forty, Eleanor V. J.; Hartley, Susan E.; Nielsen, Uffe N.; Tissue, David T.; Johnson, Scott N. (Frontiers in Plant Science, 2016)
and contrasting levels of root herbivory